From can see to can't : Texas cotton farmers on the southern prairies - Sitton, Thad, 1941-; Utley, Dan K. (Austin, Tex : University of Texas Press, 1997)
This book offers a view of Texas farming in the late 1920s. From breaking ground, to planting, cultivating and harvesting, to how the family lives, their houses, food and clothing.
Introduction -- Texas cotton -- Lay of the land -- Midwinter -- In the fields -- Picking, ginning, and hog killing -- Epilogue: a world ends.
Includes bibliographical references (pages 297-308) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Farm life -- Texas -- Fayette County; Farm life -- Texas -- Washington County; Cotton farmers -- Texas -- Fayette County; Cotton farmers -- Texas -- Washington County; Ethnology -- Texas -- Fayette County; Ethnology -- Texas -- Washington County; Fayette County (Tex.) -- Social life and customs; Washington County (Tex.) -- Social life and customs; Oral history; Farm life -- Texas -- Fayette County; Farm life -- Texas -- Washington County; Vie à la ferme -- Texas -- Fayette; Vie à la ferme -- Texas -- Washington (Comté); Producteurs de coton -- Texas -- Fayette; Producteurs de coton -- Texas -- Washington (Comté); Ethnologie -- Texas -- Fayette; Ethnologie -- Texas -- Washington (Comté); Histoire orale; oral histories (literary genre); HISTORY -- State & Local -- General; HISTORY / United States / State & Local / General; Cotton farmers; Ethnology; Farm life; Manners and customs; Oral history; Texas -- Fayette County; Texas -- Washington County; Katoenproductie; Boeren; Dagelijks leven; Farm life -- Texas -- Fayette County; Farm life -- Texas -- Washington County; Cotton farmers -- Texas -- Fayette County; Cotton farmers -- Texas -- Washington County; Ethnology -- Texas -- Fayette County; Ethnology -- Texas -- Washington County; Fayette County (Tex.) -- Social life and customs; Washington County (Tex.) -- Social life and customs; Oral history; Cotton farmers -- Texas -- Fayette County; Cotton farmers -- Texas -- Washington County; Ethnology -- Texas -- Fayette County; Ethnology -- Texas -- Washington County; Farm life -- Texas -- Fayette County; Farm life -- Texas -- Washington County; Fayette County (Tex.) -- Social life and customs; Oral history; Washington County (Tex.) -- Social life and customs; Oral history